2021
DOI: 10.3389/fphar.2021.726490
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Metformin Use in Rheumatoid Arthritis: A Randomized Controlled Study

Abstract: Objective: To evaluate the efficacy and safety of metformin use in rheumatoid arthritis (RA) patients receiving conventional synthetic disease modifying anti-rheumatic drugs (csDMARDs).Methods: A prospective, randomized, controlled, single blinded, study was carried on 66 RA patients with moderate and high disease activity state, receiving csDMARDs. Patients were simply randomized to receive either metformin 850 mg twice daily (Metformin group, n = 33), or placebo twice daily (Control group, n = 33) in additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Although a large number of studies have shown that metformin treatment can reduce inflammation, delay disease progression, protect bone tissue, and improve metabolic dysfunction and immune system function in the progression of RA [ 24 , 50 , 51 , 52 , 53 , 54 ], few studies focus on the relationship between metformin treatment and the risk of RA. In an 18-year retrospective cohort study, Naffaa found that adherence to metformin therapy reduced the risk of RA, but this conclusion was limited to women alone [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a large number of studies have shown that metformin treatment can reduce inflammation, delay disease progression, protect bone tissue, and improve metabolic dysfunction and immune system function in the progression of RA [ 24 , 50 , 51 , 52 , 53 , 54 ], few studies focus on the relationship between metformin treatment and the risk of RA. In an 18-year retrospective cohort study, Naffaa found that adherence to metformin therapy reduced the risk of RA, but this conclusion was limited to women alone [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metformin modulates immune response, autophagy, mitophagy, endoplasmic reticulum (ER) stress, and apoptosis and exerts epigenetic effects [ 21 ]. Many studies have shown that metformin treatment can reduce the severity of RA [ 22 , 23 , 24 ]. Chen [ 25 ] demonstrated metformin can effectively inhibit RA-FLS (fibroblast-like cells) proliferation through inducing the cell cycle and up-regulating and down-regulating p70s6k and 4E-BP1 phosphorylation, thus reducing the severity of RA in his study.…”
Section: Introductionmentioning
confidence: 99%
“…Marcucci et al., theorize that high concentrations of metformin may have an immunostimulatory effect (such as in tumour cells, where it is allowed to accumulate) and low concentrations have an immunosuppressive effect ( Marcucci et al., 2020 ). Evidence exists for metformin use in treatment of both tuberculosis and rheumatological diseases, suggesting that metformin may even be a safer alternative to TNF inhibitors ( Gharib et al., 2021 ; Kim et al., 2022 ). In addition, metformin also facilitates phagolysosome fusion in macrophages indicating that there is further potential for metformin to aid infections caused by intracellular pathogens, such as M. tuberculosis ( Singhal et al., 2014 ; Wallis and Hafner, 2015 ; Rana et al., 2021 ; Bone et al., 2021 ).…”
Section: Effects Of Existing and Potential Immunomodulators On Pneumo...mentioning
confidence: 99%
“…Due to the complexity of the disease, the current understanding of the pathophysiology and therapeutics for RA is still limited. For instance, although a large number of studies have shown that metformin treatment can reduce inflammation, delay disease progression and protect bone tissue in the RA progression, few studies focus on the relationship between metformin treatment and the risk of RA (5). Epidemiologic studies suggested that RA contributes to the other comorbidities, such as cardiovascular diseases (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%